Outcomes of Lateral Internal Sphincterotomy for Chronic Anal Fissure - B Srujan Kumar; Amirishetty Bhaskar (Asian Journal of Medical Research, 2021)
Background: To assess outcomes of lateral internal sphincterotomy for chronic anal fissure. Subjects and Methods: Seventy- six adult patients age ranged 18- 70 years with anal fissures of either gender underwent lateral internal sphincterotomy for chronic anal fissure under general anesthesia and involved incision at the anoderm and division of a segment of the internal sphincter with electrocautery. Outcome of the treatment was evaluated. Results: There were 42 (55.2%) males and 34 (44.8%) females. Common complaint noticed in patients was pain during defecation in 78%, rectal bleeding in 44%, perianal discharge in 32, pruritis in 27 and constipation in 60%. Pain relief in 1st week was seen in 65%, in 2nd week in 72%, in 4th week in 89% and in 8th week in 95%. The difference was significant (P< 0.05). Common complications seen among patients was rectal bleeding in 3, recurrence in 2, incontinence in 1, perianal abscess in 3 and perianal hematoma in 2 patients. The difference was non- significant (P> 0.05). Conclusion: Lateral internal sphincterotomy for management of chronic anal fissure found to be effective with high healing and patient satisfaction rates and only few complications.